PENGARUH KONFLIK PERAN DAN AMBIGUITAS PERAN TERHADAP KINERJA AUDITOR DENGAN KECERDASAN EMOSIONAL SEBAGAI VARIABEL MODERASI (Studi Empiris Pada Kap Di Pekanbaru Padang dan Batam) - Patria, Rifki; Nur DP, Emrinaldi; ', Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This research aims to analyze and gets empirical prove of role conflict and role ambiguity to auditor performance with emotional quotient as moderating variable. Respondens in this research are auditors who work in public accounting firm at Pekanbaru, Padang and Batam. There 95 auditors from19 accounting firm were visited. The method of determining the sample is by using purposive sampling method, while the data processing methods used are multiple regression analysis by using SPSS version 17.00 as the software for processing data.The results of this research indicate that role conflict significantly influence auditor performance but role ambiguity does not have significant influence to auditor performance. Emotional quotient is a moderating variable between influenced of role conflict to auditor performance but it cannot be moderating between role ambiguity to auditor performance.Keyword: Role conflict, role ambiguity, emotional quotient and auditor performance